Structural Basis of Transcriptional Gene Silencing Mediated by Arabidopsis MOM1 - Nishimura, Taisuke; Molinard, Guillaume; Petty, Tom J.; Broger, Larissa; Gabus, Caroline; Halazonetis, Thanos D.; Thore, Stéphane; Paszkowski, Jerzy (PLoS genetics, 2012)
Shifts between epigenetic states of transcriptional activity are typically correlated with changes in epigenetic marks. However, exceptions to this rule suggest the existence of additional, as yet uncharacterized, layers of epigenetic regulation. MOM1, a protein of 2,001 amino acids that acts as a transcriptional silencer, represents such an exception. Here we define the 82 amino acid domain called CMM2 (Conserved MOM1 Motif 2) as a minimal MOM1 fragment capable of transcriptional regulation. As determined by X-ray crystallography, this motif folds into an unusual hendecad-based coiled-coil. Structure-based mutagenesis followed by transgenic complementation tests in plants demonstrate that CMM2 and its dimerization are effective for transcriptional suppression at chromosomal loci co-regulated by MOM1 and the siRNA pathway but not at loci controlled by MOM1 in an siRNA-independent fashion. These results reveal a surprising separation of epigenetic activities that enable the single, large MOM1 protein to coordinate cooperating mechanisms of epigenetic regulation.